The Egyptian Muslim Brotherhood and Ikhwanweb: Deliberative Ethic/Voice in a Counterpublic’s Rhetoric? - Soumia Bardhan (Journal of Deliberative Democracy)
Using counterpublic theory as framework and situating the Egyptian Muslim Brotherhood (MB) as a counterpublic, counterpublics being alternative, non-dominant publics who voice their oppositional needs and values through diverse discursive practices, the goal of this study is to: (a) Examine, in the context of the years preceding the 2011 Egyptian uprising, whether the Egyptian MB, as a counterpublic, portrays a deliberative ethic/voice in its cyber rhetoric; (b) Explore whether traditional/Western ideas of deliberation are upheld or challenged in the cyber rhetoric of the Egyptian MB; and (c) Comment on the role of Ikhwanweb, as a counterpublic sphere, in providing the Egyptian MB a space to demonstrate its deliberative potential. By looking for traits and evidences of deliberative ethic in the Egyptian MB’s cyber rhetoric—in a ‘text’ produced by an Islamist organization functioning within a secular/authoritarian socio-political ‘context’—the overarching purpose of this analysis is to make sense of : (a) an Islamist organization’s role as a counterpublic and its deliberative potential in a non-democratic setting; (b) the implications of this for thinking about deliberation between diverse groups of social agents in non-democratic cultures; and (c) the role of the Internet in facilitating counterpublics’ deliberative potential in authoritarian contexts. Thus, from a heuristic standpoint, this study is an endeavor towards contributing to a key question that animates public deliberation: how can we engage/engage with voices that hold (or are assumed to hold) anti-deliberative attitudes and/or those that operate within non-democratic socio-political contexts?